The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1807-3107bor-2015.vol29.0067
|View full text |Cite
|
Sign up to set email alerts
|

Detection of horizontal root fracture using four different protocols of cone-beam computed tomography

Abstract: The purpose of this study was to analyze four different cone-beam computed tomography (CBCT) protocols to identify horizontal root fractures (HRF) in endodontically treated teeth, with or without the presence of a metallic post. Thirty extracted single-rooted human premolars were treated endodontically. Afterwards, an observer induced a horizontal fracture in 15 teeth. Each tooth was inserted in an empty mandibular socket and submitted to a computed tomography scan taken with and without the metallic post. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…A Tomografia Computadorizada de Feixe cônico (TCFC) têm sido muito utilizada no diagnóstico e acompanhamento dos dentes traumatizados, uma vez que possibilita uma avaliação tridimensional das estruturas envolvidas 8-10, 19 . Assim como outros estudos, neste caso foi possível observar por meio dos cortes sagitais que a fratura transversa no terço médio da raiz antes observada nas radiografias periapicais, apresentava-se oblíqua na tomografia 8 .…”
Section: Discussionunclassified
“…A Tomografia Computadorizada de Feixe cônico (TCFC) têm sido muito utilizada no diagnóstico e acompanhamento dos dentes traumatizados, uma vez que possibilita uma avaliação tridimensional das estruturas envolvidas 8-10, 19 . Assim como outros estudos, neste caso foi possível observar por meio dos cortes sagitais que a fratura transversa no terço médio da raiz antes observada nas radiografias periapicais, apresentava-se oblíqua na tomografia 8 .…”
Section: Discussionunclassified
“…In our study, we used a small FOV and the 2 smallest voxel sizes available in the CBCT scan to analyze the furcation area and obtained good results in both protocols. Accordingly, Salineiro et al11 observed that proportional FOV and voxel size resulted in better diagnosis results.…”
Section: Discussionmentioning
confidence: 99%
“…Endodontically treated teeth present intracanal metallic posts, and dental implants may produce artifacts in CBCT images 11. These artifacts are represented by radiopaque, radiolucent, and bright tracks that can overlap the teeth12 or bone and mimic bone loss 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root fractures have become diagnosable since 1896 when twodimensional (2D) radiography was introduced to dentistry (Li et al 2002). However, if the angle of the projection is not perpendicular to the fracture line, these fractures may remain undiagnosed (Salineiro et al 2015).…”
Section: Introductionmentioning
confidence: 99%